2022
DOI: 10.1007/s11356-022-23290-4
|View full text |Cite
|
Sign up to set email alerts
|

Neonicotinoid exposure in Tricolored Blackbirds (Agelaius tricolor)

Abstract: There is increasing awareness of the negative ecological and environmental effects of widespread use of pesticides on the landscape. Spillover or drift of pesticides from agricultural areas has been shown to impact species health, reproduction, and trophic dynamics through both direct and indirect mechanisms. Neonicotinoid insecticides are associated with observed declines of insectivorous and grassland birds, and these environmental pollutants are a significant conservation concern for many species that have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Status of Neonicotinoid Pollution in Japan 2018; Takeuchi and Nishizawa, 2018;Nishino et al, 2018;Yamamuro et al, 2019;Graves et al, 2023). Moreover, a couple of biomonitoring studies have consistently reported neonicotinoids in humans and other nontarget vertebrates (Ueyama et al, 2015;Harada et al, 2016;Kabata et al, 2016;Osaka et al, 2016;Honda et al, 2019;Ikenaka et al, 2019;Ospina et al, 2019;Tao et al, 2019a;Tao et al, 2019b;Zhang et al, 2019b;Li and Kannan, 2020;Li et al, 2020c;Song et al, 2020;Wang, et al, 2020a;Nimako et al, 2021;Oya et al, 2021;Taira et al, 2021;Nimako et al, 2022;Shinya et al, 2022).…”
Section: Neonicotinoid Insecticidesmentioning
confidence: 99%
See 3 more Smart Citations
“…Status of Neonicotinoid Pollution in Japan 2018; Takeuchi and Nishizawa, 2018;Nishino et al, 2018;Yamamuro et al, 2019;Graves et al, 2023). Moreover, a couple of biomonitoring studies have consistently reported neonicotinoids in humans and other nontarget vertebrates (Ueyama et al, 2015;Harada et al, 2016;Kabata et al, 2016;Osaka et al, 2016;Honda et al, 2019;Ikenaka et al, 2019;Ospina et al, 2019;Tao et al, 2019a;Tao et al, 2019b;Zhang et al, 2019b;Li and Kannan, 2020;Li et al, 2020c;Song et al, 2020;Wang, et al, 2020a;Nimako et al, 2021;Oya et al, 2021;Taira et al, 2021;Nimako et al, 2022;Shinya et al, 2022).…”
Section: Neonicotinoid Insecticidesmentioning
confidence: 99%
“…At present, reports of massive consumption rates and high environmental ubiquity of neonicotinoid-containing formulations have sparked several concerns about their potential adverse effects on biodiversity. These concerns are justified as neonicotinoid spillovers or drifts from agricultural areas could contaminate various ecological habitats and pose risks to species' populations, health, reproduction, and trophic dynamics (Graves et al, 2023).…”
Section: Neonicotinoid Exposures In Ecological Species Of Japanmentioning
confidence: 99%
See 2 more Smart Citations